Unique or universal? Mechanisms and processes of social change in post-socialist Warsaw - Górczyńska, Magdalena (Hungarian Geographical Bulletin, 2014)
This paper aims at providing new knowledge about the processes and dynamics of socio-spatial changes in post-socialist cities through the example of Warsaw. As reference cities for comparison we use two other post-socialist capital cities, Budapest and Prague. Dynamics in urban space are investigated through (1) the socio-spatial differentiation of neighbourhoods; (2) the regeneration of old housing stock in the inner-city, as well as (3) differentiation of actors contributing to new housing construction. These processes influence residential mobility and shape significantly the spatial distribution of different social groups. Their impact on Warsaw has been assessed based on quantitative data. According to our research findings the process of property restitution, accompanied by privatisation and a growing mix of ownership structure, induced a unique process of fragmentation and social segregation at a micro-scale in the inner city of Warsaw, while the socio-spatial consequences of suburbanisation have been more similar to other post-socialist cities.